PENENTUAN ONGKOS ANGKUT TOTAL MINIMUM - Elfreda Aplonia Lau (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2019)
This study emphasizes the way to determine the optimal transportation costs (minimum) by using the transportation method. This research was conducted on the consideration that the presence of transportation methods has helped managers in calculating total transportation costs, so that products can be distributed with optimal / minimum total costs. Determination of minimum total freight costs is certainly one of the strategies used in competition, namely the price suppression strategy. Low freight costs provide opportunities for entrepreneurs to determine low selling prices. There are 4 initial table methods prepared in allocating temporary loads from a source to a destination. The four initial table methods are North West Corner Method (NWCM), Least Cost Method (LCM), Vogel Aproximation Method (VAM) and Russell Aproximation Method (RAM). The optimal test for whether or not the distribution with the initial table is done using the Stepping Stone method and the Modified Distribution method. The availability of these methods encourages to assess whether the determination of the total freight costs is based on the North West Corner Method, the Least Cost Method, the Vogel Aproximation Method, the Russell Approximation Method which has the same effect on the optimal (Minimum) transportation costs when measured by Stepping Stone Method and / Distribution Method? Among the Stepping stone methods and the Modified Distribution Method give the same or different decisions in making a decision on the choice of transportation method? How is it used? Illustration of the use of transportation methods in determining the optimal total freight costs based on Yanel company data concluded that: First, determining the total freight cost based on the North West Corner Method, the Least Cost Method, the Vogel Application Method, the Russell Approximation Method does not necessarily have the same effect on the optimal (Minimum) transportation costs measured by the Stepping Stone Method and / Distribution Method. Second, optimal testing (minimum freight) with the Stepping stone Method and Modified Distribution Method gives the same decision so that organizations or companies that want to apply the transportation method in determining the minimum total freight costs can choose between stepping stone and modified distribution testing methods. Third, selection the initial table method and the test method depend on the user, which method is most easily understood